2019
DOI: 10.31234/osf.io/h8tju
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Confidence Database

Abstract: Understanding how people rate their confidence is critical for characterizing a wide range of perceptual, memory, motor, and cognitive processes. However, as in many other fields, progress has been slowed by the difficulty of collecting new data and the unavailability of existing data. To address this issue, we created a large database of confidence studies spanning a broad set of paradigms, participant populations, and fields of study. The data from each study are structured in a common, easy-to-use format th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Because confidence is known to correlate negatively with response times 75,76 (RT), we first explored a potential relationship between the two and asked whether RTs could have served as a proxy for performance. We ran a Bayesian linear regression model of participants' confidence ratings including the RT as a fixed effect and random intercepts for participant and facial expression, as well as a per-participant random slope for RT.…”
Section: Machine Learning -Effects Of Rtmentioning
confidence: 99%
“…Because confidence is known to correlate negatively with response times 75,76 (RT), we first explored a potential relationship between the two and asked whether RTs could have served as a proxy for performance. We ran a Bayesian linear regression model of participants' confidence ratings including the RT as a fixed effect and random intercepts for participant and facial expression, as well as a per-participant random slope for RT.…”
Section: Machine Learning -Effects Of Rtmentioning
confidence: 99%
“…If that 26 choice had been correct, the participant received 1 €, and 0 € otherwise. This payoff method 27 ensured participants kept a stable performance and did not relax their attention or 28 automatized their responses during some trials. 29 30…”
Section: Manipulation Of Task Difficulty (Experiments 1-4) 33mentioning
confidence: 99%
“…= 0.001, p = 0.022) 24 and in expected performance (p = 0.180) between the two tasks were included as predictors 25 in the same regression. Second, we compared this regression model with a simpler one that 26 only included the difference between tasks in expected performance and in actual accuracy, 27 and we found that the model including confidence explained the data significantly better than 28 the model without confidence (log-likelihood: full model = -2266.989, no confidence model = 29 -2529.497; χ²(1) = 525.015, p < 0.001). Third, in a different but similar approach, we could 30 predict priority from confidence (p < 0.001) in a regression in which we included as an offset 31 the prediction of priority by expected performance and actual accuracy.…”
mentioning
confidence: 99%
See 2 more Smart Citations